Controls on Terrigenous Detritus Deposition and Oceanography Changes in the Central Okhotsk Sea Over the Past 1550 ka - Chou, Yu-Min; Jiang, Xiaodong; Lo, Li; Wang, Liang-Chi; Lee, Teh-Quei; Wang, Chun-Chieh; Pan, Yongxin; Zou, Jianjun; Humbert, Fabien; Liu, Zhiqiang (Frontiers in Earth Science, 2021)
The Okhotsk Sea, which connects the high latitude Asian continent and the North Pacific, plays an important role in modern and past climate changes due to seasonal sea ice coverage and as a precursor of the North Pacific Intermediate Water. The long-term glacial-interglacial changes of sea ice coverage and its impacts on terrigenous transport and surface primary productivity in the Okhotsk Sea remain, however, not well constrained. On the basis of the marine sediment core MD01-2414 (53°11.77′N, 149°34.80′E, water depth: 1,123 m) taken in the central Okhotsk Sea, we reconstruct the terrigenous sediment transport and paleoceanographic variations during the past 1550 thousand years ago (ka). Seventeen geomagnetic excursions are identified from the paleomagnetic directional record. Close to the bottom of the core, an excursion was observed, which is proposed to be the Gilsa event at ~1550 ka. During glacial intervals, our records reveal a wide extension of sea ice coverage and low marine productivity. We observed ice-rafted debris from mountain icebergs composed of coarse and high magnetic terrigenous detritus which were derived from the Kamchatka Peninsula to the central Okhotsk basin. Still during glacial intervals, the initiation (i.e., at ~900 ka) of the Mid-Pleistocene Transition marks the change to even lower marine productivity was observed, suggesting that sea-ice coverage became larger during the last 900 ka. During interglacial intervals, the central Okhotsk Sea was either devoid in sea-ice or the ice was at best seasonal; resulting in high marine productivity. The weaker formation of Okhotsk Sea Intermediate Water, lower ventilation, and microbial degradation of organic matter depleted the oxygen concentration in the bottom water and created a reduced environment condition in the sea basin. The freshwater supplied by snow or glacier melting from Siberia and Kamchatka delivered fine grain sediments to the Okhotsk Sea. During the stronger interglacial intervals after the Mid-Brunhes Transition (i.e., Marine Isotope Stages 1, 5e, 9, and 11), strong freshwater discharges from Amur River drainage area are in association with intensified East Asian Summer Monsoon. This process may have enhanced the input of fine-grained terrigenous sediments to the central Okhotsk Sea.